2020
DOI: 10.1007/s11420-019-09746-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Patient Recovery after THA or TKA using Mobile Technology

Abstract: Background Smartphones offer the possibility of assessing recovery of mobility after total hip or knee arthroplasty (THA or TKA) passively and reliably, as well as facilitating the collection of patient-reported outcome measures (PROMs) with greater frequency. Questions/Purposes We investigated the feasibility of using mobile technology to collect daily step data and biweekly PROMs to track recovery after total joint arthroplasty. Methods Pre- and post-operative daily steps were recorded in prospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Previous studies have demonstrated the benefits of continuous measurement within the recovery process following cardiac [31] and neurological surgery [32]. This feature should be considered for orthopedic interventions, where quantifying the progress can motivate patients to take active roles in their recovery [33]. Mehta et al [34] aligned this idea with reports of positive reinforcement by setting and meeting individual recovery goals following hip arthroplasty.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Previous studies have demonstrated the benefits of continuous measurement within the recovery process following cardiac [31] and neurological surgery [32]. This feature should be considered for orthopedic interventions, where quantifying the progress can motivate patients to take active roles in their recovery [33]. Mehta et al [34] aligned this idea with reports of positive reinforcement by setting and meeting individual recovery goals following hip arthroplasty.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Researchers have established that using a fast-track, streamlined educational protocol or a recovery instant messaging, educational application can reduce the rate of readmission in patients undergoing TJR (Bahadori et al, 2020; Berg et al, 2018; Campbell et al, 2019; Gabor et al, 2020; Hussain et al, 2017; Lyman et al, 2020; Stauber et al, 2020; Timmers et al, 2019; Zheng et al, 2019). A common theme among all articles was that same-day outpatient TJR patients who received adequate and streamlined perioperative education had fewer readmissions in the 30-day postoperative period.…”
Section: Results and Discussion Characterization Of The Body Of Liter...mentioning
confidence: 99%
“…The observational study by Lyman et al . found that a smartphone app following TKA was able to collect step data on a median of 92% of days for men and 86% of days for women for 6 months following surgery ( 30 ). However, this study excluded a high proportion of patients who do not usually carry their phones, which may have biased the results toward greater compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The PainCoach app improved pain control and decreased opioid use in the 2 weeks following TKA (29). The Moves app successfully collected complete 6-month follow-up data from 68% of patients, a rate that was considered satisfactory by the authors (30). When creating these appbased platforms, priority should be placed on creating personalized information based on the user's postoperative day, which was shown to increase physical functioning and decrease pain compared to standard informational apps (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation